2012
DOI: 10.1007/s00296-012-2421-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on a study of health-related quality of life in patients with rheumatoid arthritis

Abstract: There are studies about health-related quality of life (HRQoL) in patients with rheumatoid arthritis (RA), but few studies prospectively assessed HRQoL. The main purpose of this study was to analyze HRQoL in patients hospitalized due to RA exacerbation and observed over a planned 2-year follow-up in an outpatient setting. The study involved 42 women and 9 men, at mean age of 62.5 years (SD ± 12.6). The mean duration of the study was 22–23 months. The HRQoL analysis was performed using the SF-36 survey. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…6 General measures of QOL, such as the Health Assessment Questionnaire Disability Index (HAQ) and the Short-Form 36 , as well as disease-specific measures, such as the RAQOL and the QOL-RA, all indicate poorer QOL than controls. [7][8][9][10][11] The influence of psychosocial factors on QOL in RA has been documented in samples from various countries.…”
Section: Introductionmentioning
confidence: 99%
“…6 General measures of QOL, such as the Health Assessment Questionnaire Disability Index (HAQ) and the Short-Form 36 , as well as disease-specific measures, such as the RAQOL and the QOL-RA, all indicate poorer QOL than controls. [7][8][9][10][11] The influence of psychosocial factors on QOL in RA has been documented in samples from various countries.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases influence the patients' QoL due to the diversity of symptoms, medication-related complications, and psychotic and social dysfunctions. Also, SLE and RA patients experience various limitations, including physical, psychological, and social disabilities, which can affect different aspects of health-related QoL (HRQoL) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…As such, in an effort to attain parsimony and based on theoretical plausibility, this path was removed. The fit of this revised model was also good, S-Bχ 2 (30) = 38.59, p = .135, CFI = .977, SRMR = .062, RMSEA = .053. As shown in Figure 2, disease burden contributed to mood disturbance and higher levels of disability, whereas mood disturbance and disability related to lower levels of role functioning.…”
Section: Resultsmentioning
confidence: 85%
“…SEM results indicated that the model had excellent fit, S-Bχ 2 (30) = 38.59, p = .135, CFI = .977, SRMR = .062, RMSEA = .053. Mediational analyses demonstrated that while disease burden was associated with poor role functioning, its effects were jointly mediated by mood disturbance and disability.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation